Supporting sustainable development goals 4 through ethnoscience: Development of a scientific magazine on madurese shrimp paste - Nisak, Nafilatun; Antika, Linda Tri; Ibana, Lukluk (JPBIO (Jurnal Pendidikan Biologi), 2025)
Education that integrates local wisdom with scientific concepts is essential to create meaningful and contextual learning experiences. This study was aimed at developing and evaluating the feasibility of a scientific magazine based on the ethnoscience of Madurese shrimp paste as a biology learning medium for class X at Islamic Senior High School (MA). The method employed was the Research and Development (R&D) 4-D model (Define, Design, Develop, Disseminate). The validation process showed a very high level of feasibility, with an average score of 92.5% from two subject matter experts, 93% from two media experts, and 95% from a biology teacher. In addition, the limited trial involving 30 students resulted in an average feasibility score of 93.4%. The results indicated that the scientific magazine based on the ethnoscience of Madurese shrimp paste was highly feasible as an alternative teaching material, contextual, engaging, and supportive of biology learning within the Merdeka Curriculum. Furthermore, the product was considered to have strong potential to enhance scientific literacy and promote the preservation of local wisdom in education, especially in support of SDG 4.